2021
DOI: 10.3390/cryst11040408
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Porous Structure in Autoclaved Materials Modified by Glass Sand

Abstract: This paper describes the use of glass sand in the production of autoclaved bricks. Traditional autoclaved materials consist of SiO2, CaO, and H2O. The purpose of the tests is to analyze the possibility of using glass sand in autoclaved materials and to determine their properties and durability. Depending on the structure, building materials can have porosities ranging from 0% (glass, metals) to over 90% (thermal insulation materials such as aerated concrete). Porosity of materials is directly related to the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…This difference may be associated with the fact that quartz sand is less reactive because it has a higher Mosh hardness (7) and can scratch glass [ 53 ]. The material strength was in the range of 10–20 MPa (the compressive strength test was the subject of the previous article [ 2 , 3 ]); therefore, it was similar to the reference brick, but the glass-modified material was more compact and uniform. The analysis of voids in the traditional silicate brick sample treated as the reference value showed that the pore content below 300 µm represented 0.02%, i.e., 0.06 mm 3 , while in the sample modified with recycled glass sand, it represented 0.8%, i.e., 2.5 mm 3 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This difference may be associated with the fact that quartz sand is less reactive because it has a higher Mosh hardness (7) and can scratch glass [ 53 ]. The material strength was in the range of 10–20 MPa (the compressive strength test was the subject of the previous article [ 2 , 3 ]); therefore, it was similar to the reference brick, but the glass-modified material was more compact and uniform. The analysis of voids in the traditional silicate brick sample treated as the reference value showed that the pore content below 300 µm represented 0.02%, i.e., 0.06 mm 3 , while in the sample modified with recycled glass sand, it represented 0.8%, i.e., 2.5 mm 3 .…”
Section: Resultsmentioning
confidence: 99%
“…At this point, however, the possibility of injecting mercury into the bottle pores should be considered without drastically destroying the structure of the material. The maximum pressure of 420 MPa is necessary to force mercury into pores with a diameter of 0.006 µm [ 3 ]. Assuming that the destructive pressure is close to the tensile strength of the tested material, with mercury penetration into the pores with radius dimensions ≤ 0.02 µm, the damage process will begin, changing the image of the actual pore distribution in the tested material.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An example of such a solution is the use of ground chalcedonite [ 24 , 25 ], ground limestone [ 26 ], dolomite powder [ 27 ], metakaolinite [ 28 ], barium [ 29 ], bentonite [ 30 ], thermally activated Carboniferous shale [ 31 ] and silica fume [ 32 ]. In recent years, the impact of waste glass in silicates has been extensively studied [ 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%